The Doomed, the Post-, and the Exact Curve of the Thing: Tao Lin in the After. Issue 3 (December 2015) - Ardoin, Paul
Abstract : This article reads the potential of the literary text to challenge and exceed the limits of the conventionally literary, moving toward the realm of what we might understand, in fact, as the counter textual or post -literary. It locates this post-literary potential in Tao Lin's post-9/11 collection Bed, which itself focuses on periods of post ness as affectively marked. Following recent work in theories of affect, this paper reads Bed as invested in art's potential to transform negative affects into productive action. In the case of Lin's text, this work lies both in its content and in a form characterised by a distinctive brand of metaphor that heeds T. E. Hulme's modernist call 'to get out the exact curve of the feeling or thing', alongside a devotion to a conspicuously anti-literary flatness Lin has described as the 'concrete slash literal'.